Efflux Pumps and Multidrug-Resistance in Pyricularia oryzae Triticum Lineage - Vicentini, Samara Nunes Campos [UNESP]; Moreira, Silvino Intra [UNESP]; da Silva, Abimael Gomes [UNESP]; de Oliveira, Tamiris Yoshie Kiyama [UNESP]; Silva, Tatiane Carla [UNESP]; Assis Junior, Fabio Gomes [UNESP]; Krug, Loane Dantas [UNESP]; de Paiva Custódio, Adriano Augusto; Leite Júnior, Rui Pereira; Teodoro, Paulo Eduardo; Fraaije, Bart; Ceresini, Paulo Cezar [UNESP] (MDPI, 2022)
Widespread resistance to QoIs, DMI and SDHIs fungicides has been reported for Brazilian populations of the wheat blast pathogen Pyricularia oryzae Triticum lineage (PoTl). A pre-existing resistance mechanism not associated with target site mutations has been indicated for resistance to DMIs and SDHIs, with strong indication that PoTl has multidrugresistance (MDR). Therefore, the main objective of this study was to test the hypothesis that resistance to DMI and SDHI fungicides detected in PoTl was due to efflux pump mediated MDR mechanism(s) by characterizing the sensitivity to antifungal efflux pump substrates. Four antifungal substrates were tested: tolnaftate (TOL), cycloheximide (CHX), rhodamine 6G (RH6G) and triphenyltin chloride (TPCL). TPCL and RH6G were considered the most relevant indicators for enhanced MDR activity. Among the 16 PoTl isolates tested, 9 were insensitive to TPCL, 1 to TOL, 16 to RH6G and 1 to CHX. The PoTl isolates were grouped into four distinct multidrug resistance phenotypes (MDRPs) based on resistance to combinations of fungicides and antifungal efflux pump substrates. Insensitivity to TPCL, RH6G and or TOL correlated well with DMI insensitivity, but MDR was not associated with SDHI resistance. The identification of multiple MDRP phenotypes associated with DMI resistance in our study warrants further research aimed at revealing the exact mechanisms of multidrug resistance in the wheat blast pathogen, including efflux pumps overexpression via transcriptomic analyses of differentially expressed genes; identification and discovery of mutations associated with changes in promoter regions or transcription factors of efflux transporters associated with multidrug resistance.
Keywords: DMI; MDR; QoI; SDHI; wheat blast